NCMP-05. RITUXIMAB AS INITIAL THERAPY FOR THE REVERSAL OF MYASTHENIA GRAVIS NEUROTOXICITY CAUSED BY IPILIMUMAB/NIVOLUMAB. (5th November 2018) - Verma, Neha; Jaffer, Muhammed; Peguero, Edwin; Mokhtari, Sepideh
Abstract: BACKGROUND: In patients with melanoma treated with immune checkpoint inhibitors (ICIs), neurological toxicities developed in 1% treated with Ipilimumab and 3% after Nivolumab. This rises to 14% when co-administered. Patients treated with ICIs are susceptible to Myasthenia Gravis like syndrome. There are several case reports that demonstrate the benefits of rituximab in both acetylcholine receptor (AChR) and muscle specific kinase (MuSK) antibody-positive MG patients. This study demonstrates the benefit of Rituximab in early goal therapy. OBSERVATION: A 70 year old female with scalp dermal spindle cell melanoma participating in a clinical trial with Nivolumab versus Ipilimumab/Nivolumab presented with diplopia. She suffered from shortness of breath and intermittent bilateral eye ptosis. Her ophthalmologic symptoms started following cycle one of therapy. Her ophthalmologist and allergist felt she had allergies. Her symptoms worsened with generalized muscle weakness and horizontal diplopia. One year later, her neurologist diagnosed her with Myasthenia Gravis. She did not receive treatment and had difficulty contacting her neurologist. She saw her pulmonologist for worsening dyspnea and her pulmonary function test showed a decreased negative inspiratory force (NIF) < 20 cm H2O. She declined admission and was treated with Mestinon 60 mg q4hr and prednisone 90 mg. Her NIF and FVC did not improve and she was given IVIG for 5 days. Her PFTs had only slightly improved. She received 1 dose of Rituximab at 375 mg/m2 and her FVC improved to >2.5 L. She was discharged on prednisone 40 mg daily and Mestinon 60 mg TID. Three days after Rituximab she was completely asymptomatic. DISCUSSION: Our case study shows a patient treated with immune checkpoint inhibitors developed Myasthenia gravis like syndrome and was successfully treated with Rituximab. CONCLUSION: Our study shows the importance of Rituximab as initial therapy for the reversal of MG like syndrome caused by Ipilimumab/Nivolumab.